The Fiddlers of James Bay - Rodgers, Bob (Office national du film du Canada, 1980)
This short documentary traces the history of the fiddle’s arrival in Canada 300 years ago via Scottish traders from Orkney Island. The Cree population of what is now Northern Québec adopted the instrument, and many contemporary Cree residents are master fiddlers. In this film, two Cree fiddlers travel to the Orkney Islands, the birthplace of the music they learned from their fathers and grandfathers. The film captures the warmth and good will of this reunion.